2022
DOI: 10.1186/s12891-022-05685-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a telehealth physiotherapist-delivered intensive dietary weight loss program combined with exercise in people with knee osteoarthritis and overweight or obesity: study protocol for the POWER randomized controlled trial

Abstract: Background Obesity is associated with knee osteoarthritis (OA). Weight loss, alongside exercise, is a recommended treatment for individuals with knee OA and overweight/obesity. However, many patients cannot access weight loss specialists such as dietitians. Innovative care models expanding roles of other clinicians may increase access to weight loss support for people with knee OA. Physiotherapists may be well placed to deliver such support. This two-group parallel, superiority randomized contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Meanwhile, telerehabilitation strategies, including educational lectures, medical suggestions, and psychotherapy were effective for the reduction of pain [ 23 ]. Furthermore, Bennell et al [ 49 ] suggested that telehealth-delivered exercise and diet programs improved pain in people with knee OA and overweight or obesity, which indicated that diet also plays an important role in alleviating pain in patients with knee OA. These telerehabilitation programs could combine various interventions to ease pain.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, telerehabilitation strategies, including educational lectures, medical suggestions, and psychotherapy were effective for the reduction of pain [ 23 ]. Furthermore, Bennell et al [ 49 ] suggested that telehealth-delivered exercise and diet programs improved pain in people with knee OA and overweight or obesity, which indicated that diet also plays an important role in alleviating pain in patients with knee OA. These telerehabilitation programs could combine various interventions to ease pain.…”
Section: Discussionmentioning
confidence: 99%
“…This was a two-group, superiority, parallel-design randomised controlled trial (RCT) prospectively registered (Clinicaltrials.gov NCT04733053), protocol published,20 approved by the University of Melbourne Human Research Ethics Committee (HREC 1955042). The only change to trial methods was allowing participants to self-report follow-up body weight over the telephone using their own scales if they were unable to attend follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Participant satisfaction with their intervention was assessed using a seven-point global rating scale (‘extremely dissatisfied’ to ‘extremely satisfied’, ‘moderately’ or ‘extremely’ satisfied, categorised as ‘satisfied’). Other process measures collected and a nested qualitative study of participants and physiotherapists20 will be reported separately.…”
Section: Methodsmentioning
confidence: 99%